Optimizing Local Economic Potential to Increase Regional Food Security through Village-Owned Enterprises Empowerment (Mixed Method: Explanatory Sequential Design) - Rahmat Alhakim; Hakim Hakim; Inam Fakhrul Mujab; Reza Nur Fitriani (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to identify and optimize local economic potential to strengthen regional food security through the empowerment of Village-Owned Enterprises (BUMDes) in Cilacap Regency. Using a mixed-method explanatory sequential design, quantitative analysis was conducted through Klassen Typology, Static and Dynamic Location Quotient (LQ–DLQ) to identify base and prospective agricultural commodities across sub-districts. The results were further elaborated using the Analytic Hierarchy Process (AHP) involving key stakeholders. The findings indicate that rice remains a permanent base commodity, while cassava, soybeans, and sweet potatoes show strong potential for future development. Strategic priorities emphasize food diversification, institutional strengthening of BUMDes, and multi-stakeholder collaboration to support regional food security and the Free Nutritious Meal (MBG) program